The Translation Problem Types in Translating Indonesia Text to English (A Case Study of Translation Subject of Fifth Semester English Students –UPY) - Sujatmiko Sujatmiko (Universitas PGRI Yogyakarta, 2017)
This research is entitled “The Translation Problem Types in Translating Indonesia textinto English (A Case Study of Translation Subject of Fifth Semester English Department –UPY) . It is about how Indonesia text is translated into English by English students, toidentify the translation problems, and to identify the problematics of translation technique.This research uses qualitative method to analyze the data. Techniques of analyzing datain this research consist of 3 components, they are (1) reducing the data, (2) explaining thedata, and (3) taking a conclusion. Reducing data is a process of selecting, focusing,simplifying and abstracting the data. Explaining the data is a process of organizinginformation and arranging the complete narration. Taking a conclusion is a process ofdrawing conclusion from the data. The data source of this research are Indonesia text andstudent’s translation.After conducting the research, the research find the data that all respondents havesimilar translation problem types in translating Indonesia text into English. The problems arediction, tenses, no equivalence translation; others have problems of adverb, article, andrelative clause. None of respondents apply other translation technique. They only apply wordper word translation technique. The accuracy of transfer level is adequate level. Only onerespondent have almost completely successful transfer level. Other respondents haveadequate accuracy transfer level. By applying the untrue translation technique has an impactto translation accuracy transfer level.This research is expected to open wide opportunities and challenges to academicians,especially those in translation linguistics sphere to deepen their research and study, especiallyin translating Indonesia text to English in order to be a new contribution to the translationfields.